PERANAN LEMBAGA PEMASYARAKATAN DALAM MEMBINA MENTAL NARAPIDANA KHUSUS ANAK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DI LEMBAGA PEMBINAAN KHUSUS ANAK PEKANBARU - HARRY ADRIAN; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
On April 27, 1964, as the home of Indonesia's prison has been converted into a correctional institution in accordance with the idea of Sahardjo who at that time served as justice minister. In the penal system, inmates and students correctional entitled to receive physical education and guarantee their rights to perform worship, dealing with outsiders it family or other parties, obtaining information through print and electronic media, a proper education and so forth , To get it all is the main task of implementing the law, among others, the Correctional Institution. The purpose of writing this essay, namely; First, to determine the role of the Agency is to foster the child's special mental prisoners under Act No. 11 of 2012 on the Criminal Justice System Child Development Institute for Special Children Pekanbaru. Second, to determine the mechanism of character development in the correctional institution inmate mental menbina special child. Third, to determine the factors that cause mental development of children has not been executed at the Institute for Special Children Pekanbaru. This type of research is a sociological research, because the authors of the study on the effectiveness of the laws in force. This research was conducted at the Correctional Institute Children Pekanbaru city, while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews, questionnaires and literature study. From the research problem there are two main things that can be inferred. First, the role of the State Children's Correctional Institute Pekanbaru (LPKA) in the implementation of the rights of students / inmates have not been implemented to the fullest. Second, the mechanism of mental coaching LPKA Pekanbaru performed in conjunction with the guidance mechanism. Third, Barriers to mental coaching run LPKA is about infrastructure and budget issues. Advice writer, First, the role of which do LPKA should be implemented to the maximum in accordance to Law Number 11 Year 2012 on Juvenile Justice System. Second, the mechanism of mental coaching is not supposed to be united with the skills and education training mechanism. Third, barriers should not be an obstacle for Law No. 11 Year 2012 on Juvenile Justice System already regulate the rights of students / inmates of children.Keywords: Inmates - Coaching - Mental - Children